2023
DOI: 10.1039/d2bm00881e
|View full text |Cite
|
Sign up to set email alerts
|

PDAC-on-chip for in vitro modeling of stromal and pancreatic cancer cell crosstalk

Abstract: Pancreatic ductal adenocarcinoma (PDAC) mainly develops in the head of the pancreas, within the acino-ductal unit composed by acinar and ductal cells surrounded by pancreatic stellate cells (PSCs). PSCs strongly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…After injection, the constructs were placed in 24-well plates, with enough cell medium to keep them hydrated, but not enough to cover the entry of the lumen, to prevent HPDE cells from floating into the media. Co-cultures were maintained in DMEM/F-12 supplemented with 15% FBS (Gibco), 1% Penicillin-Streptomycin (Gibco) and 2% L-glutamine (Gibco) since previous tests demonstrated the efficacy of this culture medium composition in promoting the cell viability 86 . Two hours later, more medium was added to the wells, this time covering the full constructs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After injection, the constructs were placed in 24-well plates, with enough cell medium to keep them hydrated, but not enough to cover the entry of the lumen, to prevent HPDE cells from floating into the media. Co-cultures were maintained in DMEM/F-12 supplemented with 15% FBS (Gibco), 1% Penicillin-Streptomycin (Gibco) and 2% L-glutamine (Gibco) since previous tests demonstrated the efficacy of this culture medium composition in promoting the cell viability 86 . Two hours later, more medium was added to the wells, this time covering the full constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Co-cultures were maintained in DMEM/F-12 supplemented with 15% FBS (Gibco), 1% Penicillin-Streptomycin (Gibco) and 2% L-glutamine (Gibco) since previous tests demonstrated the efficacy of this culture medium composition in promoting the cell viability 103 . the constructs were kept in a humidified CO 2 incubator at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…We further assessed the a-SMA expression, which is a common biomarker of CAFs, 51,52 in the desmoplastic PDAC spheroids to explore whether normal fibroblasts were activated and obtained the CAF phenotype during co-culturing. Fig.…”
Section: Bioprinting Of Pdac Tumor Spheroidsmentioning
confidence: 99%
“…Another study employed a multilayer PDAC-on-chip design to culture PDAC cells, PSCs, and fibroblasts in separate compartments. The findings revealed that fibroblasts altered their morphology to a myofibroblast-like shape and secreted increased amounts of IL-6 in the presence of cancer cells, potentially modeling the early steps of PDAC evolution ( Sgarminato et al, 2023 ). The incorporation of vascularization into tumor-chips is a crucial strategy to mimic proper in vivo physiology, particularly for PDAC where high interstitial pressure leads areas of vascular collapse and poor perfusion.…”
Section: Current Microphysiological Systems Of ‘Cold’ Tumorsmentioning
confidence: 99%